Host-shifts at family level in the Australian Acacia-thrips lineage (Thysanoptera, Phlaeothripinae) with two new species - Mound, Laurence A.; Wells, Alice (Zootaxa, 2020)
The Australian Acacia-thrips lineage comprises at least 250 species in 30 genera of Phlaeothripinae, all of them known only from Acacia species in Australia. Two new species from two of these genera are described here as the first recorded instances of host-shifting within this diverse thrips lineage, with the host shifts being between unrelated angiosperm orders, from Fabales to Proteales and Myrtales. Brakothrips eucalypti sp. n. is described from the branches of a species of Eucalyptus, and Katothrips banksiae sp. n. is described forming substantial colonies within lepidopterous leaf mines on a species of Banksia. Previously these thrips genera were known only from Acacia species, and comprised seven described species of Brakothrips and 35 described species of Katothrips.